Guanyin can understand Pali: Cross-traditional practices of Indonesian Buddhists who worship Guanyin through Pali Paritta - Buaban, Jesada; Makin, Al; Sutrisno, Evi Lina (Humanities, Arts and Social Sciences Studies, 2025)
In the 1960s–1990s, Buddhism in Indonesia had to adapt significantly to state policies. Chinese cultures and Mahayana Buddhism were marginalized because they were seen as obstacles to assimilation into Indonesian identity. This resulted in significant growth of Theravada Buddhism. This article addresses two questions: (1) how did Chinese communities who were forced to adopt Theravada Buddhism maintain their beliefs in public areas? and (2) how have Buddhist monks in the Buddhayana organization, the largest and most adaptable Buddhist group in Indonesia, adjusted their teachings to serve the needs of Chinese communities? The research is based on document study of Buddhist magazines published since the 1960s and ethnographic fieldwork conducted through residence in Buddhayana temples in Java for two years (2021–2022). The figure of Guanyin, in terms of history, development, and worship in Indonesia, serves as the central theme to illustrate the adaptation of Buddhist rituals using the concepts of hybridity and interspirituality. The study has two major findings. (1) Although Chinese Buddhists chant in Pali, the veneration of Guanyin has not been abandoned. The Theravada Paritta is used as a medium to worship the Mahayana Bodhisattva. (2) While other Buddhist groups may view this practice as a form of mixed or syncretic Buddhism, Buddhayana followers interpret it as a cross-tradition practice rather than syncretism. For them, true Buddhism lies in its teachings, not in rituals, which may be contextually adaptable. The adaptive approach of Buddhayana monks aligns with the Mahayana ideal that Guanyin can manifest in any form to help sentient beings. The commitment to liberate beings from suffering should not be confined by language or culture. Ultimately, this article argues that Guanyin symbolizes not only a cross-gender and cross-national deity but also a cross-sectarian figure that enables practitioners to transcend boundaries of religious traditions.